Does celiac disease impair coronary microvascular circulation: Coronary flow velocity reserve of patients with celiac disease. Issue 1 (9th December 2019) - Caliskan, Zuhal; Telci Caklili, Ozge; Kahraman, Resul; Ozcan, Fatma Betul; Sayar, Suleyman; Kostek, Osman; Demircioglu, Kenan; Yilmaz, Yusuf; Kul, Seref; Caliskan, Mustafa
Abstract: Background: Celiac disease (CD) is an enteropathy characterized with immune reaction to gliadin protein. Aim: In this study, we aimed to assess effect of CD on coronary microvascular circulation and the association between coronary flow velocity reserve (CFVR) and hs‐CRP/Albumin ratio. Material and Methods: Study was conducted between March 2017 and November 2018 with CD at Umraniye Training and Research Hospital Gastroenterology Clinic. CFVR was defined as the ratio of hyperemic to baseline diastolic peak velocities. CFVR ≥ 2.0 was considered normal. C‐reactive protein/albumin ratio (CAR) was calculated as hs‐CRP/albumin. Results: Serum albumin (4.27 ± 0.56 vs 4.50 ± 0.34; P value: .04) level was significantly lower in celiac group but higher Hs‐CRP (2.44 ± 1.24 vs 1.82 ± 1.29; P value < .01), hs‐CRP/albumin ratio (0.57 ± 0.30 vs 0.41 ± 0.31; P value: .03) were recorded in celiac group. Both hyperemic flow and CFVR substantially lower in the celiac group compared to controls. In univariate analysis; age, hs‐CRP, and hs‐CRP/albumin ratio were associated with low CFVR and hs‐CRP/albumin level was an accurate predictor of low CFVR at the ROC curve. Conclusion: In this study, we found that in patients with CD, coronary flow reserve is impaired.